Performance of Social Goods in the Indian Banking sector and its Impact - K., Prabhavathi; G. P., Dinesh (Prabandhan: Indian Journal of Management, 2023)
Purpose : The objective of the present article was to investigate corporate social responsibility (CSR) activities in the Indian banking industry. This study empirically examined the relationship between the two variables, CSR spent and net profits after tax of public and private sector banks, and how CSR by banks contributed to producing value in society. Methodology : The study examined the key CSR initiatives â€” social, environmental, women’s empowerment, employment, healthcare, and education, independently carried out by banks, and the CSR spent was taken as independent variables. Further, sustainability and net profits after tax as the financial performance were considered to be the dependent variables. For the study, annual reports from the years 2018 â€“ 2021 were considered, and the analysis was conducted using the Pearson coefficient on NCSS 2022. Findings : This analysis highlighted a correlation between an organizationâ€™s annual CSR spending and its subsequent year’s net profits after tax. Banking is crucial to the social and economic advancement of India. Practical Implications : This study suggested that additional research in this field of CSR in the banking sector be conducted as banks have a well-defined structure to meet social demands and are working extremely hard to meet their goals. Originality : Unlike the prior research on CSR, the present work created a relationship between the social performance and the financial performance of the companies irrespective of any industry and their step toward sustainability.